1996
DOI: 10.1002/(sici)1097-0142(19960615)77:12<2622::aid-cncr28>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of morbidity and mortality in 60 patients with peritoneal carcinomatosis treated by cytoreductive surgery and heated intraoperative intraperitoneal chemotherapy

Abstract: BACKGROUND.Peritoneal carcinoma has been regarded as a uniformly lethal clini-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(79 citation statements)
references
References 28 publications
4
72
1
2
Order By: Relevance
“…19 One treatment approach is cytoreductive surgery combined with the intraperitoneal administration of cytotoxic agents. 20 This may diminish any residual tumor after macroscopic excision and may overcome the pharmacokinetic limits of systemic chemotherapy. Intraperitoneal chemotherapy gives high response rates within the abdomen because the ''peritoneal plasma barrier'' provides doseintensive therapy 21 since high-molecular-weight substances are confined to the abdominal cavity for long time periods.…”
Section: Discussionmentioning
confidence: 99%
“…19 One treatment approach is cytoreductive surgery combined with the intraperitoneal administration of cytotoxic agents. 20 This may diminish any residual tumor after macroscopic excision and may overcome the pharmacokinetic limits of systemic chemotherapy. Intraperitoneal chemotherapy gives high response rates within the abdomen because the ''peritoneal plasma barrier'' provides doseintensive therapy 21 since high-molecular-weight substances are confined to the abdominal cavity for long time periods.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of consensus about the optimal target temperature and a finding of increased morbidity and mortality when a cytoreduction procedure has been followed by hyperthermic i.p. chemotherapy (Jacquet et al, 1996) that warrant further studies. To optimise the i.p.…”
Section: Discussionmentioning
confidence: 99%
“…The series with extended peritonectomies combined with IPCH reported a mortality rate of 5% and a morbidity rate of 35%, pointing out the fact that duration of surgery and the number of digestive anastomoses performed were correlated with a higher morbidity rate. 18 As far as indications are concerned, we no longer include patients with unresectable primary tumor as we did at the beginning of our experience. The best indications of IPCH seem to be peritoneal carcinomatosis with small malignant granulations (Stage I and II), and peritoneal carcinomatosis in patients for whom debulking surgery (granulation exeresis or local peritonectomies) appears to be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have confirmed the existence of preferential flows inside the abdominal cavity, 12 and here is probably the reason for some bowel complications reported by various authors. 18,21 These preferential flows may induce very high local temperatures as well as very high local drug concentrations.…”
Section: Homogeneous Diffusion Of Heat and Drugs Insidementioning
confidence: 99%